2012
DOI: 10.1007/s11187-012-9442-z
|View full text |Cite
|
Sign up to set email alerts
|

Succession financing in family firms

Abstract: Business succession is one of the primary management challenges for family firms. However, many family firms fail at this task because of financial issues. Although a vast number of studies have investigated the succession process, research thus far has failed to determine how and why family firms select particular forms of financing for succession-related expenditures. Accordingly, this study conceptually and empirically investigates succession financing. We introduce a conceptual framework that investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 92 publications
(142 reference statements)
1
24
0
3
Order By: Relevance
“…By considering this information the family business owner is able to ascertain what the current and future economic viability of the business is. Economic viability will be important because it will determine what type of succession the owners are willing and able to engage in [40,50]. The second type of business information to consider would be organizational size.…”
Section: Contextual Factors Influencing Evaluations Of Succession Tramentioning
confidence: 99%
See 1 more Smart Citation
“…By considering this information the family business owner is able to ascertain what the current and future economic viability of the business is. Economic viability will be important because it will determine what type of succession the owners are willing and able to engage in [40,50]. The second type of business information to consider would be organizational size.…”
Section: Contextual Factors Influencing Evaluations Of Succession Tramentioning
confidence: 99%
“…Finally, this paper also has important implications for understanding other decisions during the succession process. For example, the work of Koropp and colleagues [50] suggests that transactions costs during a succession process can affect how succession occurs. Thus, financial resources can impact the decisions of what type of succession to engage in.…”
Section: Implications Of Our Succession Intent Modelmentioning
confidence: 99%
“…For example, Adedayo et al [10] showed that the founder's proactiveness in the succession plan and the founder's experience improve the sustainability of the firm. Although the importance of early succession planning is widely acknowledged [11][12][13], few firms actually have succession plans in place [14,15]. A particularly striking finding was reported by Diwisch et al [16], who found no significant differences in performance between firms that plan for succession in the following 10 years and those that do not, thereby refuting the negative or positive implications of early succession planning.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, studies have shown that IFSI is associated with family influence and commitment to the business (Holt, Rutherford, & Kuratko 2010), family firms' access to debt financing (Chua, Chrisman, Kellermanns, & Wu 2011;Koropp, Grichnik, & Gygax 2013), and have identified IFSI as a key determinant of family-oriented particularistic behavior (Zellweger et al 2012). To repeat, flowing out of this body of knowledge is the important fact that IFSI influences family firm behavior whether or not IFS actually takes place later.…”
Section: Introductionmentioning
confidence: 99%